2022
DOI: 10.1177/17488958221128933
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perceptions of domestic, intimate partner violence and the government’s interventions in Nigeria: A qualitative study

Abstract: Domestic violence, including intimate partner violence, increased exponentially following the Covid-19 pandemic. Nonetheless, there appears to be a paucity of research that draws on a social constructionist theoretical lens to explore women’s perspectives of the Nigerian government’s interventions addressing such violence. The study recruited 24 purposively selected female participants from Delta state, Nigeria. Informed by a social constructionist thematic analysis, findings revealed that they were a perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Women autonomy, economic status and household decision making ability as a predictor of IPV has continue to yield conflicting results in studies conducted in Nigeria [21,51]. Various theoretical models have been used to explain predictors of IPV [11,16]. Interventions should include implementation of existing laws and policies against IPV and active client-oriented screening for IPV in health facilities [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women autonomy, economic status and household decision making ability as a predictor of IPV has continue to yield conflicting results in studies conducted in Nigeria [21,51]. Various theoretical models have been used to explain predictors of IPV [11,16]. Interventions should include implementation of existing laws and policies against IPV and active client-oriented screening for IPV in health facilities [45].…”
Section: Discussionmentioning
confidence: 99%
“…Some few studies however, demonstrated that physical violence is the most common type of violence encountered in the country [14]. IPV is on the increase especially following COVID 19 Pandemic [16]. Within Nigeria regional and geographical differences has been reported in different studies with Emotional/psychological Violence occurring more in the conservative northern societies than physical that is most seen in the more educationally advanced southern states [15].…”
Section: Prevalencesmentioning
confidence: 99%